TEKNOLOGI FIREBASE UNTUK APLIKASI LAPOR AKAKOM - Rudy Cahyadi; Ariesta Damayanti; Irwan Setiawan (JURNAL INFORMATIKA DAN KOMPUTER, 2019)
The mechanism for conveying aspirations in STMIK AKAKOM by academicians and how the responses given have not been able to run well. This happens because the media used to convey these aspirations are only through suggestion boxes or by conveying them directly to the parties concerned. The follow-up given by the related parties was felt to still take a long time. Therefore, the application of aspirations and information is needed to accommodate the aspirations and dissemination of information by utilizing Firebase technology. Some features used in making this application are Firebase Firestore to make data updates in real time and the application can be used offline. Firebase Cloud Messaging is used to create push notifications. This application is divided into two parts. The web-based application functions to manage information and aspirations used by the admin of STMIK AKAKOM and the Android-based application functions to receive information and send aspirations to be used by STMIK AKAKOM students. The results of this study are the application of aspirations and information by utilizing Firebase technology. From the testing that has been done, it is obtained that the application can function as an application to manage student reports and aspirations.